PELAKSANAAN PROGRAM DESA MAJU INHIL JAYA (DMIJ) BIDANG SARANA INFRASTRUKTUR DI DESA LIMAU MANIS KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR TAHUN 2015 - Ayu Amalia; Tuti Khairani Harahap (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Program of Desa Maju Inhil Jaya is the superior program of the government periode 2013-2018. The objectives of this program are to escalate the prosperety and the opportunity of getting job for the people of the region by encourage the independence to determine the decision and the management of the sustainable development. The implementation of this program involved the people of the region such as planning, implementation, and maintenance due to increase the success of this program especially in infrastructure developmente of the region.The objective of this research is to find out the implementation of Desa Maju Inhil Jaya (DMIJ) program in infrastructure facility at Desa Limau Manis kecamatan Kemuning Kabupaten Indragiri Hilir by 2015. This research was conducted by using qualitative methoede and the data assessement by using descriptive methode. In collecting the data the writer used interview, observation and documentation of the key person in charge as the information resource.This reaearche showed that Desa Maju Inhil Jaya program in infrastructure facility at Desa Limau Manis Kecamatan Kemuning Kabupaten Indragiri Hilir 2015 contributed the advantage for the people, even though the implementation has not worked well due to limited human resource and cost to develope the infrastructure, and the lacked of people participation.Keywords: Impelemtation, Desa Maju Inhil Jaya, Infrastructure facility